2003
DOI: 10.2166/wqrj.2003.007
|View full text |Cite
|
Sign up to set email alerts
|

Actinomycetes in the Elbow River Basin, Alberta, Canada

Abstract: Actinomycetes can produce significant amounts of the earthy-muddy odour compounds geosmin and 2-methylisoborneol (MIB). These filamentous bacteria are found in both terrestrial and aquatic environments, and are particularly abundant in soil. They can enter freshwater systems via terrestrial runoff and subsequently cause taste and odour outbreaks in drinking water. Since it is well known that actinomycete growth and odour production is modified strongly by environmental factors such as moisture and nutrient lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 25 publications
0
14
0
1
Order By: Relevance
“…Hoson and coworkers also found that the dissolved 2-MIB fraction was larger than the cell-bound fraction (32). In some cases, allochthonous soil runoff may be important (33,113). Biofilms can also be very significant sources, even in large, fast-flowing rivers.…”
Section: Intra-and Extracellular Voc Fractionsmentioning
confidence: 99%
See 3 more Smart Citations
“…Hoson and coworkers also found that the dissolved 2-MIB fraction was larger than the cell-bound fraction (32). In some cases, allochthonous soil runoff may be important (33,113). Biofilms can also be very significant sources, even in large, fast-flowing rivers.…”
Section: Intra-and Extracellular Voc Fractionsmentioning
confidence: 99%
“…The genus Streptomyces is widely used synonymously with odor-producing actinomycetes, but it is important to note that nonstreptomycete actinomycetes such as Nocardia are also potent producers of both geosmin and 2-MIB, while many streptomycetes are nonproducers (112). The two compounds are principal odor components of soil (9,40), and periods of high terrestrial runoff may introduce actinomycetes and/or their odorous metabolites into surface waters, causing episodic odor outbreaks in rivers, particularly in areas of intensive livestock operations (33,37,112,113).…”
Section: Biological Origins Of Geosmin and 2-mibmentioning
confidence: 99%
See 2 more Smart Citations
“…Actinomycetes, which can grow in autumn and winter (Lanciotti et al, 2003), might be responsible for the production of these earthy/musty odor causing compounds. Actinomycetes might also enter freshwater systems via terrestrial runoff, and subsequently cause T/O outbreaks in drinking water (Zaitlin et al, 2003).…”
Section: Evaluation Of Typical Odorous Compoundsmentioning
confidence: 99%